2021
DOI: 10.1186/s40594-021-00299-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sources of engineering teaching self-efficacy for pre-service elementary teachers

Abstract: Background The Next Generation Science Standards (2013) put a special emphasis on engineering for K-12 science education. However, a significant number of elementary teachers still feel unprepared to integrate engineering into their science programs. It is, therefore, incumbent upon science educators to update their elementary science methods courses to accommodate engineering especially in the states which adopted the NGSS. In this study, we taught an engineering unit in an elementary science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This could adversely affect the teachers' ability to plan, teach and assess students during STEM lessons. This finding was not unique to the Thai teachers as many other studies (Dong et al, 2020;El Nagdi & Roehrig, 2020;Yesilyurt et al, 2021) have reported on STEM teachers' apprehension and confusion when tasked to teach STEM lessons due to a range of issues and challenges including the differences in the structure and scope of the knowledge and practices from the traditional monodisciplinary lessons, their lack of knowledge in managing these differences, and the lack of support to implement STEM lessons. The teachers may only have knowledge of the specific STEM disciplines which they were trained to teach (Ramliet al, 2017).…”
Section: 2mentioning
confidence: 73%
“…This could adversely affect the teachers' ability to plan, teach and assess students during STEM lessons. This finding was not unique to the Thai teachers as many other studies (Dong et al, 2020;El Nagdi & Roehrig, 2020;Yesilyurt et al, 2021) have reported on STEM teachers' apprehension and confusion when tasked to teach STEM lessons due to a range of issues and challenges including the differences in the structure and scope of the knowledge and practices from the traditional monodisciplinary lessons, their lack of knowledge in managing these differences, and the lack of support to implement STEM lessons. The teachers may only have knowledge of the specific STEM disciplines which they were trained to teach (Ramliet al, 2017).…”
Section: 2mentioning
confidence: 73%
“…Therefore, gender may not have meaningful influence on participants' science teaching efficacy beliefs. Negatively stated items (3,6,8,10,13,17,19,20,21,23) were not reverse scored in this table.…”
Section: Resultsmentioning
confidence: 99%
“…In their research [12] on self-efficacy and support strategies for teachers, experienced teachers reported higher self-efficacy in the areas of instructional strategies and classroom management and lower for student engagement. In the same perspective, Yesilyurt, Deniz and Kaya [13] studied the instructional strategies and learning experiences that worked to improve pre-service elementary teachers' use of engineering education intervention. Their study indicated that incorporating engineering design activities with explicit-reflective instruction for engineering concepts has the potential to improve pre-service teachers' personal engineering teaching efficacy beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…They also help test hypotheses, show multiple representations, provide numerous solutions (Li et al, 2016), communicate with social processes and foster motivation for learning (Gero & Danino, 2016). Yesilyurt et al (2021) indicated that mastery of cognitive content and pedagogy were important sources for trainee teachers' engineering teaching efficacy.…”
Section: Theoretical Background Teaching Science Through Engineering ...mentioning
confidence: 99%